GAMBARAN PENYESUAIAN PSIKOLOGIS PADA INDIVIDU PASCA CEDERA OTAK: A SCOPING REVIEW - Nabella, Abigail; Mukhlina, Nova; Syifa Paramitha Divani, Prajna; Jauza, Nabila; Amira Mulika, Rifda; Khakim, Zulfikri; Wimbarti, Supra (Universitas Nusantara PGRI Kediri, 2024)
This scoping review explores the psychological adjustment of individuals after brain injuries, focusing on its impact on cognitive, emotional, and social functions, as well as the factors that influence recovery. Relevant literature was sourced from databases like PubMed and Google Scholar using search terms such as “acquired brain injury,”